Penguatan Literasi Koding dan AI melalui Platform Hour of Code : Studi Kasus: Program AI Ready ASEAN pada Siswa SMK di Ponorogo - Ardiansyah, Amiril; Fillah, Asyirah Mujahidah (PELITA NUSA TENGGARA, 2026)
Digital literacy in Ponorogo is still low, with a score of only 38.60 according to the Indonesian Digital Society Index (IMDI). This situation shows that we need to help local students improve their digital skills. This project aims to help students understand the basics of coding and Artificial Intelligence (AI) through a simple training program. The training took place at three schools: SMK Wahid Hasyim Ponorogo, SMK BAKTI Ponorogo, and SMK PGRI 1 Ponorogo. The research method is qualitative descriptive, with data analysis techniques referring to the Miles & Huberman approach, and implementation designed through four integrated stages: 1) information dissemination and program offering, 2) preparation and amplification, 3) training implementation, and 4) training evaluation. The results demonstrate significant improvements post-training, including coding/AI literacy (30% to 90%), AI perception (59% to 82%), AI usage intention (50% to 95%), coding/AI learning motivation (37% to 95%), and intention for advanced learning (93% to 94%). These findings affirm that targeted training programs are effective in enhancing technology literacy for students in the region, while supporting national digital literacy acceleration.